The Effect of Colonialism on Implementation of Agrarian Reform in Indonesia - Ricco Andreas; Luthfi Kalbu Adi; Sri Sulastuti (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
The agrarian carried by Sukarno was supported by the peasants throughout Indonesia. How not, the agrarian basic law which then came into force on 1 January 1961 aims to restore and redeem (redistribution) agricultural land to each head of the farm family. The step for that begins with determining the maximum and minimum area of agricultural land taking into account the population, area and other factors. But in its journey, agrarian reform was also influenced by Indonesia's political situation. The problem that will be discussed by the researcher is How do the elements of colonialism influence the implementation of Agrarian Reform in Indonesia? The research method used is a normative legal research method. With the ovary desk, in-depth interviews with related parties. The results of the study are: In addition to the evidence that still uses the Positief Wettelijk system, the state through its tools also puts forward repressive methods as a method of handling agrarian conflicts. So that it can be said that the "spirit" of the custom of the colonial government until now is still "carried" by the state. This has a big influence on the operation of the legal system, and the application of the Agrarian Principles Law in agrarian reform.